2014
DOI: 10.1038/onc.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein aggregation promotes platinum resistance in ovarian cancer

Abstract: High-grade serous ovarian carcinoma (HGSOC), the most lethal gynecological cancer, often leads to chemoresistant diseases. The p53 protein is a key transcriptional factor regulating cellular homeostasis. A majority of HGSOCs have inactive p53 because of genetic mutations. However, genetic mutation is not the only cause of p53 inactivation. The aggregation of p53 protein has been discovered in different types of cancers and may be responsible for impairing the normal transcriptional activation and pro-apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 53 publications
(67 reference statements)
2
109
1
Order By: Relevance
“…These cells lost the capacity for p53 aggregation and tumor development when they differentiated into chemosensitive progenies. Because p53 aggregation was dependent on the overexpression of p14ARF in the stem cell lines, its inhibition resulted in suppression of p53 aggregation (Yang-Hartwich et al 2015). It seems that WT p53 behaves as a mutant conformation in stem cells of HGSOC.…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregationmentioning
confidence: 99%
See 3 more Smart Citations
“…These cells lost the capacity for p53 aggregation and tumor development when they differentiated into chemosensitive progenies. Because p53 aggregation was dependent on the overexpression of p14ARF in the stem cell lines, its inhibition resulted in suppression of p53 aggregation (Yang-Hartwich et al 2015). It seems that WT p53 behaves as a mutant conformation in stem cells of HGSOC.…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregationmentioning
confidence: 99%
“…Using a different strategy, Yang-Hartwich et al (2015) found that WT p53 in stem cells of HGSOC also had the property to aggregate. These cells lost the capacity for p53 aggregation and tumor development when they differentiated into chemosensitive progenies.…”
Section: New Approaches For Cancer Therapy Involving P53 Aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…Building up on their previous work on the role of p53 aggregation in p53 inactivation and platinum resistance, 17 Yang Yang-Harwitch, PhD (Yale University), Gil Mor, MD, and colleagues presented their recent work on the relationship between transcription factor Twist1 and p53 in mediating EMT and metastasis (manuscript not published). Twist1 has been associated with EMT promotion, enhanced migration, and CSC status.…”
mentioning
confidence: 99%